Economic challenges and problems related to natural resources management as a consequence of human capital accumulation - MAKHOVA, L. A; LAPINSKAS, A. A; HAYKIN, M. M (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The current study considers the evolution of the concept of human capital over time. The theory of human capital was shaped from research results obtained by foreign economists. Thus, it covers many independent existing aspects that should also be studied independently. This article draws special attention to the impact of abundant natural resources on the accumulation of human capital. The article analyzes modern theories through the lens of an idea that economic growth is dependent upon the abundance of natural resources. The institutional factor also plays a role in this relationship, so classic economic theories were considered as well. RESUMEN El presente estudio considera la evolución del concepto de capital humano a lo largo del tiempo. La teoría del capital humano se formó a partir de los resultados de la investigación obtenidos por economistas extranjeros. Por lo tanto, cubre muchos aspectos independientes que deberían estudiarse también de forma independiente. Este artículo llama especialmente la atención sobre el impacto de los abundantes recursos naturales en la acumulación de capital humano. El artículo analiza las teorías modernas a través de la idea de que el crecimiento económico depende de la abundancia de recursos naturales. El factor institucional también juega un papel en esta relación, por lo que también se consideraron las teorías económicas clásicas.